Islanding Detection and Enhancement of Microgrid Performance - Pouryekta, A.; Ramachandaramurthy, K.; Mithulananthan, N.; Arulampalam, A. (IEEE, 2017)
Nowadays, renewable energy sources (RES) are widely used in the distribution system. Despite the advantages of RES in the system, they also introduce some problems such as unintentional islanding, protection concerns, reverse power flow, etc. Due to the unpredictable faults or scheduled maintenance plans, a distribution system can be sectionalized into several islands provided that enough dispersed generation units are available. Thus, distribution systems should be capable of detecting islanding condition for smooth transition to an islanded mode. As a first step, an islanding detection method (IDM) is proposed in this paper to detect the islanding phenomenon in a distribution system. The proposed method is a hybrid IDM which consists of a remote detection method and a passive method. In the next step, an adaptive control strategy is proposed to ensure stable operation of islanded subsections. The proposed method utilizes error rates of system parameter such as voltage and power to readjust generator controllers and maintain the system stability. The proposed IDM and adaptive controller are implemented on a generic distribution network using EMTDC/PSCAD software. Results have shown that the hybrid detection method is capable of detecting the islanding in the presence multiple distributed generation units. Moreover, the proposed IDM is not affected by load/generation changes. Results also showed a smooth transition from grid-connected mode to autonomous operation mode. Furthermore, the proposed adaptive control strategy maintains stable operation of the island when fault occurs in the island.
Keywords: Terms—Control of islands; islanding detection